Analisis kaitan Syekh Burhanuddin dan Kadar Ali dengan tradisi tabut: bulan Muharam di Bengkulu-Pariaman - Japarudin Japarudin; Een Syaputra (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Tabut in Bengkulu and Tabuik in Pariaman are two traditions that have the same socio-historical background, namely the Karbala incident in 61 AH. However, regarding the figure who originated this tradition at that time, until now there has been no clarity. This research aims to describe and analyze Syech Burhanudin and Kadar Ali in Bengkulu and Pariaman and their relationship to the Tabut Tradition. This research was conducted as a qualitative type of research. Data collection was carried out through interviews, a literature study, documentation, and observation. Data analysis was carried out using the Milles and Huberman interactive model. The results of the research show that Syech Burhanuddin (I, II, and III), who is known in West Sumatra, has no connection with Syech Burhanuddin in Bengkulu and also has no connection with the Tabut tradition in Bengkulu and Pariaman; Kadar Ali from Pariaman and Kader Ali from Bengkulu are suspected to be the same person in two possible schemes. Kadar Ali originally came from Bengkulu, migrated to Pariaman, and developed the Tabut tradition, but then returned to Bengkulu and died in Bengkulu. Second, Kader Ali is a native of Pariaman who married, then brought his wife to Pariaman and developed Tabut.